The pursuit of happiness an economy of well-being - Graham, Carol, 1962-; ebrary, Inc. (Washington, D.C. : Brookings Institution Press, 2011)
"Focuses on the role in the policymaking process of new metrics for measuring the effects on individual well-being of institutional, macroeconomic, and policy environments--for example, the effects of macroeconomic uncertainty and lack of access to health insurance--as well as the effects of factors such as commuting time, divorce, job status, and obesity"--Provided by publisher.
Happiness : a new science -- What we mean by happiness : a "theory" of agency and well-being -- Happiness around the world : what we know -- Adaptation and other puzzles -- GNH versus GNP?.
Includes bibliographical references and index.
Electronic reproduction.
Keywords: Economics -- Psychological aspects; Happiness; Quality of life; Uncertainty; Electronic books